Rancang Bangun Sistem Informasi General Ledger Dana Sosial Didukung Fasilitas SMS (Studi Kasus: PKPU Cabang Surabaya) - Mochammad Arifin; Jeviliyan Rahma Citra.D (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
The use of information system has spread rapidly along with the increasing need for well-integratedinformation. PKPU as one of social foundations in Surabaya gives facility in fundraising given by the donorsand then distributes them to the poor, such as tsunami victims, flood victims, etc. Now, PKPU is still using excelto do their financial reports. The researcher found many weaknesses in using excel to do these. It needs a longtime to find the donors’ data. PKPU does not produce profit and loss report, instead PKPU produces balancereport. To solve the problems above, there should be a system that can help fundraiser and the person in theaccounting department in making financial report. Based on the testing, the researcher concludes thatinformation system for social funding general ledger supported by sms facility is the solution to the problemsdealing with computerized financial report. This is because this system can create financial reportautomatically. For example, it can be used to make journal report, ledger report, etc. In addition, since thissystem is suppported by SMS facility, this system can give easier information to the donors.Kata Kunci: information system, ledger, accounting, sms